Integrasi Micro-Apps Individual menjadi One-Stop Services Maranatha Application Suite - Joseph Sanjaya; Erick Renata; Vincent Elbert Budiman; Francis Anderson; Mewati Ayub (Jurnal Teknik Informatika dan Sistem Informasi, 2019)
Use of information systems at the university, which is the standard management of the university, is required to support all the activities of the academic community. Aside of determining the smooth operations, information technology also maintain the competitiveness of the competitors by constantly updating the information technology so as not to miss. Trends in the development of technology will make a strong connectivity between universities and stakeholders, governments, and partners. Some of the problems that occur when information systems are not yet fully integrated system, separate user management, application is implemented on different platforms and dashboards for management, not integrated. It is important for the university to provide Single and Integrated Application applications that are integrated into each of their services. Single and Integrated Applications are available at the web application / desktop / mobile multi-platform, for which data are available in real time, and there is no duplication of data occurs.